Acetarsol in the management of mesalazine-refractory ulcerative proctitis: a tertiary-level care experience. Issue 2 (February 2019) - Argyriou, Konstantinos; Samuel, Sunil; Moran, Gordon W.
Abstract : Background: Mesalazine-refractory ulcerative proctitis is common, with a significant proportion of the patients requiring escalation to immunomodulators or biological therapy. Three small preliminary cohort studies suggested good clinical efficacy for the organic arsenic derivative acetarsol in the management of proctitis. Our aim was to describe our experience on the use of acetarsol in proctitis and to review all existing evidence on its safety and efficacy. Patients and methods: We retrospectively reviewed clinical records of all ulcerative colitis patients exposed to acetarsol at Nottingham University Hospitals since 2012. Clinical response was determined basing on physicians' global assessments and patients' improvement over the baseline (reduction in stool frequency and rectal bleeding). Clinical remission was defined as total resolution of symptoms including bleeding cessation. Serum arsenic, C-reactive protein and faecal calprotectin levels reviewed when available. Nonparametric analysis performed. Results: Twenty-eight (16 males) patients with median (range) age 39 (35) and 9 (19) years disease duration received acetarsol suppositories for proctitis. All had failed mesalazine or corticosteroid topical therapy, with 50% having additionally failed immunomodulators. Median treatment duration was 70 (64) days. 16/28 were prescribed acetarsol more than once. 67.9% achieved clinical response and 46.4% clinical remission. 32.1% required treatment escalation to steroids, thiopurines or antitumour necrosis factor agents. 6/28 patients stopped acetarsol due to side effects. Conclusion: Acetarsol could be an effective and safe option in the management of refractory proctitis. A definitive trial with long-term safety follow-up is required to investigate the efficacy and safety of this promising drug.